Physical variables - lake temperature profile from Feresjön, floating platform, 2016-11-21–2022-03-24 - Asa Research Station (Swedish University of Agricultural Sciences, 2025)
High frequency temperature profiles are measured in lakes of SITES Water to be able to determine the thermal structure.
Asa Research Station (2025). Physical variables - lake temperature profile from Feresjön, floating platform, 2016-11-21–2022-03-24 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/rUxfnR2OIwHPdXKl5EiLoswK
Keywords: Asa Research Station; Lake; Time instant; Time instant; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap